2017
DOI: 10.1002/gea.21623
|View full text |Cite
|
Sign up to set email alerts
|

How much did the soldiers dig? A quantification of WW1 remains in Argonne, France

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
(36 reference statements)
1
11
0
9
Order By: Relevance
“…Integrating these soil losses over a total area of 1262 km 2 that was severely affected by WWI in Flanders resulted in a mean soil loss of 934 t/ha per the four years exceeding by more than two orders of magnitude water erosion rates. Along the more than 700 km WWI battle front (between Flanders and Alsace, France) the displaced soil volumes by shell and mine cratering and trench digging even reached values as high as 1500 to 3000 ton/ha per four years in Argonne (France; Brenot et al ., ) and locally up to 7500 ton/ha per four years (Devos et al ., ). These few case studies clearly illustrate that warfare should be recognized as a major erosion factor with explosion cratering and trench digging as major processes.…”
Section: Needs For Improved Understanding Of Natural and Anthropogenimentioning
confidence: 99%
“…Integrating these soil losses over a total area of 1262 km 2 that was severely affected by WWI in Flanders resulted in a mean soil loss of 934 t/ha per the four years exceeding by more than two orders of magnitude water erosion rates. Along the more than 700 km WWI battle front (between Flanders and Alsace, France) the displaced soil volumes by shell and mine cratering and trench digging even reached values as high as 1500 to 3000 ton/ha per four years in Argonne (France; Brenot et al ., ) and locally up to 7500 ton/ha per four years (Devos et al ., ). These few case studies clearly illustrate that warfare should be recognized as a major erosion factor with explosion cratering and trench digging as major processes.…”
Section: Needs For Improved Understanding Of Natural and Anthropogenimentioning
confidence: 99%
“…The most intensely disturbed area stands out south of the forest in the 'Quadrangle of the forts' (Fort Douaumont, Fort Vaux, Fort Souville and Fort Thiaumont), heart of the Verdun battle, and near Fort Hardaumont where significant impact densities are recorded: 100/ha at Fort Souville and up to 120/ha at Fort Douaumont which is by far the most affected fort (Pétain, 1986;Prost and Krumeich, 2015;Desrousseaux de Medrano, 2016). In comparison, Brenot et al (2017) counted up to 73 impacts/ha in Argonne and Note et al (2018) found values approaching 480 impacts/ha in Flanders, demonstrating that crater density varies greatly according to proximity to the front. For example, an average of 180 impacts/ha were recorded around the Chambrettes farm, located on the top of a hill.…”
Section: Spatial Distribution Of War Landformsmentioning
confidence: 96%
“…• In the Gruerie Wood (France), Brenot et al (2017) found shell crater sizes ranging from 1.13 to 7.61 m in diameter (Me=3.16 m) and 0.75 m in average depth. However, this brief comparative analysis is imperfect when we focus on mine craters whose morphometrics have been investigated in two other studies:…”
Section: Size Variability Of Shell Cratersmentioning
confidence: 99%
See 2 more Smart Citations